ИЗМЕНЕНИЯ ОПТИЧЕСКИХ ПАРАМЕТРОВ КРОВИ У ПАЦИЕНТОВ С ЦИРРОЗАМИ ПЕЧЕНИ РАЗЛИЧНОЙ СТЕПЕНИ ТЯЖЕСТИ - М. В. Кручинина; М. И. Воевода; С. А. Курилович; А. А. Громов; В. А. Баум; Е. Г. Немцова; Е. В. Логвиненко; Н. А. Ковалькова; В. М. Генералов; Б. Н. Зайцев; В. Н. Кручинин; С. В. Рыхлицкий; et al. (Архивъ внутренней медицины, 2014)
The optical parameters of red blood cells and serum from patients with different classes of liver cirrhosis by Child–Pugh were examined by atomic force microscopy, dielectrophoresis, spectral ellipsometry, terahertz and Raman-spectroscopy. We found that with the growth of the class of cirrhosis the level of the deformed shapes of cells with altered membrane relief was increased and transmission power terahertz suspension of erythrocytes was reduced. Among the viscoelastic and electrical parameters of erythrocytes some characteristics (summary measures of viscosity, the relative polarizability, electrical conductivity, the capacity of the cell membrane, the position of the crossover frequency) were the most important for determining the severity of liver cirrhosis. The growth of decompensation of cirrhosis resulted in lower the thickness of thin films prepared from the serum, with the rise of the refractive index and heterogeneous structure. At the same time, we observed a significant decrease of the peak areas of the absorption Raman- spectra at 1005, 1157 and 1520 cm-1.